2021
DOI: 10.1093/gerona/glab141
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Classification of Older Adults With Diabetes by Comorbidities and Exploring Relationships With Frailty, Disability, and 5-year Mortality

Abstract: Background Limited research has been conducted to risk stratify older adults with diabetes. Our objective was to re-examine the 2005-06 classification systems in participants who are now five years older. Methods We examined a subsample of 884 community-residing older adults with the diagnosis of diabetes from the National Social Life, Health, and Aging Project (NSHAP). The primary objective was to utilize a latent class anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…While Table 13.1 provides overall guidance for identifying complex and very complex patients, there is not yet global consensus on geriatric patient classification. Ongoing empiric research on the classification of older adults with diabetes based on comorbid illness has repeatedly found three major classes of patients: a healthy, a geriatric, and a cardiovascular class (9,57). The geriatric class has the highest prevalence of obesity, hypertension, arthritis, and incontinence, and the cardiovascular class has the highest prevalence of myocardial infarctions, heart failure, and stroke.…”
Section: Patients With Complications and Reduced Functionalitymentioning
confidence: 99%
“…While Table 13.1 provides overall guidance for identifying complex and very complex patients, there is not yet global consensus on geriatric patient classification. Ongoing empiric research on the classification of older adults with diabetes based on comorbid illness has repeatedly found three major classes of patients: a healthy, a geriatric, and a cardiovascular class (9,57). The geriatric class has the highest prevalence of obesity, hypertension, arthritis, and incontinence, and the cardiovascular class has the highest prevalence of myocardial infarctions, heart failure, and stroke.…”
Section: Patients With Complications and Reduced Functionalitymentioning
confidence: 99%
“…An excess risk of disability among patients with diabetes is not surprising given the associated multi‐morbidities 28,30 . As comorbidities are prevalent, 24 interventional programs promoting effective chronic disease management are indicated to promote active participation and to help delay the onset of ADL disabilities 31 .…”
Section: Discussionmentioning
confidence: 99%
“…An excess risk of disability among patients with diabetes is not surprising given the associated multi‐morbidities. 28 , 30 As comorbidities are prevalent, 24 interventional programs promoting effective chronic disease management are indicated to promote active participation and to help delay the onset of ADL disabilities. 31 Earlier studies among the US population reported that only controlling for existing comorbidities along with BMI can reduce the diabetes‐related odds by 52%.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities are common in older adults with diabetes, more than 97% of them had at least one of the comorbidities (43). Comorbidities not only increase the health care needs, utilization and mortality of people with diabetes (44)(45)(46), they also increase the complexity of disease management and the burden of self-management (47,48) which is a challenge for empty-nester patients to cope with. Decelerated physical function and care for a sick spouse in an empty-nester may be associated with reduced self-care, leading to decreased selfmanagement of diabetes.…”
Section: Discussionmentioning
confidence: 99%